Prescription Patterns of Drugs Used in Patients with Coronary Artery Disease at Tertiary Care Hospital - Fehmi M Mukadam; Ujwala P Gawali; Gawali Pranali Chavarkar; Dilara P Ali; Sanjivani Naghotkar (Research Center for Rational Use of Drugs (RCRUD), 2022)
Background: The Cardiovascular disease is emerging as one of the leading cause of morbidity and mortality worldwide. To determine the appropriateness of the prescriptions and various trends in treatment, so as to provide the basis for modification in the future drug usage in accordance with risk factors and clinical presentations and also assess the improvement of health-related quality of life of patients with coronary artery disease. Methods: A prospective, observational and cross-sectional study was conducted in Department of Pharmacology in collaboration with Department of Medicine of tertiary healthcare hospital. As per inclusion criteria, patients visiting Medicine Outpatient department (OPD) from November 2021 to January 2022 were enrolled in the study. Results: Total 360 prescriptions were analysed, most of them belonged to the age group of 61-75 years. The prevalence was higher in Females (54%) than males (46%). An average number of drugs per prescription was 4.5. All the drugs were prescribed by generic names. 90.63% drugs prescribed were included in World Health Organization (WHO) essential drugs list 2021. 98.40% drugs prescribed were included in National list of essential medicines (NLEM) 2015. Antiplatelets (99.44%) were the most commonly prescribed category of drugs, followed by hyperlipidaemic (96.67%). Conclusion: The overall analysis of prescription pattern suggests that most of the drugs were prescribed rationally according to current American College of Cardiology Federation/American Heart Association (ACC/ AHA) guidelines. The incidence of polypharmacy was in the normal limits as per WHO recommendation. Generic drugs were prescribed majorly, which promotes awareness amongst prescribers, supporting WHO policies.